2023
DOI: 10.1101/2023.01.11.23284231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammatory biomarkers and perinatal depression: a systematic review

Abstract: Background: Approximately 10 to 20% of pregnant women worldwide experience perinatal depression (PND), a depressive episode with onset during pregnancy or after childbirth. We performed a systematic review to identify, summarize and discuss studies on inflammatory biomarkers described in relation to PND. Methods: Inclusion criteria defined the selection of observational studies written in English, French, Spanish or Portuguese, that evaluate analytical levels of inflammatory molecules (protein levels) in biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…15 19-21 To capture the full path of the cross-generational transmission of child development, the identification of early risk factors for peripartum depressive symptoms has been an important topic in the field. Previous research has shown potential factors like inflammatory biomarkers (eg, increased levels of interleukin (IL)-6, IL-8, C-reactive protein (CRP) and tumour necrosis factor-α (TNF-α), see review by Silva-Fernandes et al 22 ), genetic factors (eg, serotonin transporter gene (5-HTT), catechol-O-methyl-transferase, mono-amine-oxidase type A and so on), 23 and psychosocial stressors (eg, high life stress, lack of social support, history of depression, and so on) for peripartum depression. [24][25][26][27][28] It is essential to further elucidate the longitudinal and dynamic relationship between these potential risk factors, maternal depressive symptoms and child development.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…15 19-21 To capture the full path of the cross-generational transmission of child development, the identification of early risk factors for peripartum depressive symptoms has been an important topic in the field. Previous research has shown potential factors like inflammatory biomarkers (eg, increased levels of interleukin (IL)-6, IL-8, C-reactive protein (CRP) and tumour necrosis factor-α (TNF-α), see review by Silva-Fernandes et al 22 ), genetic factors (eg, serotonin transporter gene (5-HTT), catechol-O-methyl-transferase, mono-amine-oxidase type A and so on), 23 and psychosocial stressors (eg, high life stress, lack of social support, history of depression, and so on) for peripartum depression. [24][25][26][27][28] It is essential to further elucidate the longitudinal and dynamic relationship between these potential risk factors, maternal depressive symptoms and child development.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%